2021
DOI: 10.1093/nar/gkab998
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAWiki 2.0: a knowledgebase of human long non-coding RNAs with enhanced curation model and database system

Abstract: LncRNAWiki, a knowledgebase of human long non-coding RNAs (lncRNAs), has been rapidly expanded by incorporating more experimentally validated lncRNAs. Since it was built based on MediaWiki as its database system, it fails to manage data in a structured way and is ineffective to support systematic exploration of lncRNAs. Here we present LncRNAWiki 2.0 (https://ngdc.cncb.ac.cn/lncrnawiki), which is significantly improved with enhanced database system and curation model. In LncRNAWiki 2.0, all contents are organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…LncRNAWiki ( https://ngdc.cncb.ac.cn/lncrnawiki ) is a wiki-based database for community-curation of human long non-coding RNAs (lncRNAs) ( 27 , 28 ). The current version of LncRNAWiki 2.0 is significantly updated by (i) providing a new curation model with more informative and essential annotation items, (ii) developing a new web system based on MySQL/Java (instead of MediaWiki) that is capable of organizing all contents in a structured manner, (iii) improving the community-annotation submission functionality and providing more user-friendly web interfaces and (iv) equipping with online tools for ID conversion and functional prediction.…”
Section: Recent Updatesmentioning
confidence: 99%
“…LncRNAWiki ( https://ngdc.cncb.ac.cn/lncrnawiki ) is a wiki-based database for community-curation of human long non-coding RNAs (lncRNAs) ( 27 , 28 ). The current version of LncRNAWiki 2.0 is significantly updated by (i) providing a new curation model with more informative and essential annotation items, (ii) developing a new web system based on MySQL/Java (instead of MediaWiki) that is capable of organizing all contents in a structured manner, (iii) improving the community-annotation submission functionality and providing more user-friendly web interfaces and (iv) equipping with online tools for ID conversion and functional prediction.…”
Section: Recent Updatesmentioning
confidence: 99%
“…Third, it integrates new omics features of lncRNA genes including sequence conservation across 40 vertebrates, small protein expression, and interaction with proteins. LncRNAWiki ( https://ngdc.cncb.ac.cn/lncrnawiki ), a knowledgebase of human lncRNAs, incorporates comprehensive annotations of functional lncRNAs based on a standardized curation model and provides user-friendly web interfaces to facilitate data curation, retrieval and visualization ( 54 , 55 ). This year, based on manual curation of 535 publications, we have expanded LncRNAWiki by adding 97 experiment-validated human lncRNAs, updating 191 existing lncRNAs and integrating 4761 newly-curated associations.…”
Section: Recent Updatesmentioning
confidence: 99%
“…To test KaKs_Calculator 3.0, we choose three empirical lncRNA genes that are extensively studied according to LncRNAWiki [7] and collect their human-mouse orthologs as well as their adjacent coding orthologs from NGDC LncBook [31] and NCBI RefSeq [32].…”
Section: Application On Empirical Datamentioning
confidence: 99%
“…Nowadays, a growing body of evidence have shown that non-coding sequences, historically thought as "junk" due to few knowledge on their function relative to coding sequences, are recognized as functional elements to play important regulation roles in multiple biological processes [4] and associate closely with various human diseases [5][6][7]. Albeit less conserved by comparison with coding sequences, a larger number of non-coding sequences have been identified highly conserved across mammalian genomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation